Early life adversity impaired dorsal striatal synaptic transmission and behavioral adaptability to appropriate action selection in a sex-dependent manner - de Carvalho, Gregory; Khoja, Sheraz; Haile, Mulatwa T.; Chen, Lulu Y. (Frontiers in Synaptic Neuroscience, 2023)
Early life adversity (ELA) is a major health burden in the United States, with 62% of adults reporting at least one adverse childhood experience. These experiences during critical stages of brain development can perturb the development of neural circuits that mediate sensory cue processing and behavioral regulation. Recent studies have reported that ELA impaired the maturation of dendritic spines on neurons in the dorsolateral striatum (DLS) but not in the dorsomedial striatum (DMS). The DMS and DLS are part of two distinct corticostriatal circuits that have been extensively implicated in behavioral flexibility by regulating and integrating action selection with the reward value of those actions. To date, no studies have investigated the multifaceted effects of ELA on aspects of behavioral flexibility that require alternating between different action selection strategies or higher-order cognitive processes, and the underlying synaptic transmission in corticostriatal circuitries. ELA impaired the ability to update action control in response to reward devaluation in a context that promotes goal-directedness in male mice and induced deficits in reversal learning. At the circuit level, ELA decreased corticostriatal glutamate transmission in male but not in female mice. Interestingly, in DMS, glutamate transmission is decreased in male ELA mice, but increased in female ELA mice. Overall, our findings demonstrate the sex- and region-dependent effects of ELA on behavioral flexibility and underlying corticostriatal glutamate transmission. By establishing a link between ELA and circuit mechanisms underlying behavioral flexibility, our findings will begin to identify novel molecular mechanisms that can represent strategies for treating behavioral inflexibility in individuals who experienced early life traumatic incidents.